THE INFLUENCE OF PRODUCT DIFFERENTIATION, BRAND IMAGE PREFERENCES, AND PRICE PERCEPTIONS ON PURCHASING DECISIONS FOR IPHONE SMARTPHONE PRODUCTS IN KEDIRI CITY - Cahya, Putri Aprilia; Damayanti, Susi (Universitas Nusantara PGRI Kediri, 2025)
This study's objective was to further investigate how pricing perceptions, brand image preferences, and product differentiation affect consumers' decisions to buy iPhone smartphones in Kediri City. This study employs primary data types and a quantitative methodology. A purposive selection strategy was used to choose 150 respondents for the study sample. Respondents were given a questionnaire consisting SPSSV25 was utilised to handle the data from a set of enquiries. The findings of this research demonstrate that brand image preferences, pricing perceptions, and product differences all partially and concurrently affect consumers' decisions to buy iPhone smartphones in Kediri City. This study deepens our knowledge of how marketing factors influence consumer choices. In the context of contemporary marketing for businesses, the research's impact on product differentiation, brand image preferences, and pricing perceptions is crucial. The topic of this study still comprises the city of Kediri and the single product under investigation, which is one of its limits.